2014
DOI: 10.1007/s12032-014-0332-x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial progenitor cell: a promising biomarker in clinical oncology

Abstract: Human cancers are endowed with sustained vascularization capability, and their growth, invasion, and metastasis are vascularization dependent. Recently, accumulated body of evidence suggests that endothelial progenitor cells (EPCs) can support vasculogenesis and induce angiogenesis through paracrine mechanisms. In addition, numerous clinical studies have revealed the increase in the number of EPCs in the peripheral blood of cancer patients and demonstrated the correlation of circulating EPCs (CEPCs) with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…These aspects, together with the heterogeneity of the patients series in the various studies, limit their potential to guide therapeutic strategies in clinical practice (69). In spite of these shortfalls, steps forward in the definition of the potential utility of CECs and EPCs for clinical purposes have been achieved, although reliable quantification of these cells is a work in progress and the interpretation of results must be made cautiously (35,10,70,71). In order to validate future reports that indicate, within well-designed trials, a true clinical value for both CECs and EPCs, unambiguous phenotypic definition of these cells together with careful inter-laboratory standardization of the quantitative techniques of analysis, including FCM, are mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects, together with the heterogeneity of the patients series in the various studies, limit their potential to guide therapeutic strategies in clinical practice (69). In spite of these shortfalls, steps forward in the definition of the potential utility of CECs and EPCs for clinical purposes have been achieved, although reliable quantification of these cells is a work in progress and the interpretation of results must be made cautiously (35,10,70,71). In order to validate future reports that indicate, within well-designed trials, a true clinical value for both CECs and EPCs, unambiguous phenotypic definition of these cells together with careful inter-laboratory standardization of the quantitative techniques of analysis, including FCM, are mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have shown the levels of these cells are chronically elevated in cancer patients and higher levels of these cells correlate with angiogenesis, metastases, and reduced patient survival. 48, 49 While all known cases of cancer were excluded from our analysis, chronically elevated levels of angiogenic cells in the blood of individuals living next to major roadways could be a symptom of incipient tumors, inflammation or tissue hypoxia or ongoing vascular injury; conditions that lead to a persistent increase in the circulating levels of angiogenic cells, especially when the insult is mild and does not overwhelm mobilization. We found that in individuals living <50m of a major roadway the levels of these cells were 48-65% higher than those living >50m from a major roadway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the decrease in sVEGFR2 showed an inverse linear correlation with the trough plasma levels of Nintedanib (r = -0.46). Circulating CD117-positive bone marrow derivate endothelial progenitors have been reported to contribute to tumor angiogenesis [38]. In the same study, a subset of these cells (CD45 dim CD34+CD117+) was measured in the whole blood of 15 patients after Nintedanib administration.…”
Section: Preclinical Studiesmentioning
confidence: 95%